Perancangan Video Motion Graphic 2d Layanan Call Center 110 - Iqbal Gilang Permana; Riyan Abdul Aziz; Febrianta Surya Nugraha (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Call center 110 is the right solution to deal with community emergency problems, but people don't know about it. By providing clear information, using attractive advertisements, and understanding the target audience, you can increase awareness in using call center 110 services. The research method used in this study is a qualitative method using data collection techniques: observation, interviews, literature study Video design 2D motion graphics for call center services, which will be made in mp4 format with a duration of 3–5 minutes and discuss the functions, usability and how these services work. These 110 videos consist of several police characters, as well as several designs such as trees, cities, and highways. Making 2D motion graphic videos for call center services 110 to convey news in an interesting and informative way. Through the use of elements of animation, character movement and visual effects, as well as means of communication, to inform the public about the importance of the emergency services provided by the police.